The impact of bankruptcy reform on insolvency choice and consumer credit - Jason Allen; Kiana Basiri (Bank of Canada, 2016)
We examine the impact of the 2009 amendments to the Canadian Bankruptcy and Insolvency Act on insolvency decisions. Rule changes steered debtors out of division I proposals and into the more cost-effective division II proposals. This also led to a significant substitution out of bankruptcies and into proposals. Using credit bureau data on credit card limits we test, but do not find, any evidence that this substitution into more creditor-friendly insolvencies had any impact on average lending behavior, either immediately following the amendments or up to six years removed.
Keywords: D14; G2; K35; 330; Financial system regulation and policies; Financial institutions; Credit and credit aggregates